First‐line antiretroviral therapy with efavirenz plus tenofovir disiproxil fumarate/emtricitabine or rilpivirine plus tenofovir disiproxil fumarate/emtricitabine: a durability comparison. Issue 7 (30th May 2018) - Taramasso, L; Di Biagio, A; Maggiolo, F; Tavelli, A; Lo Caputo, S; Bonora, S; Zaccarelli, M; Caramello, P; Costantini, A; Viscoli, C; d'Arminio Monforte, A; Cozzi‐Lepri, A; et al.
Abstract : Objectives: The aim of this study was to compare the durabilities of efavirenz (EFV) and rilpivirine (RPV) in combination with tenofovir/emtricitabine (TDF/FTC) in first‐line regimens. Methods: A multicentre prospective and observational study was carried out. We included all patients participating in the Italian Cohort Naive Antiretrovirals (ICONA) Foundation Study who started first‐line combination antiretroviral therapy (cART) with TDF/FTC in combination with RPV or EFV, with a baseline viral load < 100 000 HIV‐1 RNA copies/mL. Survival analyses using Kaplan–Meier (KM) curves and Cox regression with time‐fixed covariates at baseline were employed. Results: Overall, 1490 ART‐naïve patients were included in the study, of whom 704 were initiating their first cART with EFV and 786 with RPV. Patients treated with EFV, compared with those on RPV, were older [median 36 (interquartile range (IQR) 30–43) years vs . 33 (IQR 27–39) years, respectively; P < 0.001], were more frequently at Centers for Disease Control and Prevention (CDC) stage C (3.1% vs . 1.4%, respectively; P = 0.024), and had a lower median baseline CD4 count [340 (IQR 257–421) cells/μL vs . 447 (IQR 347–580) cells/μL, respectively; P < 0.001] and a higher median viral load [4.38 (IQR 3.92–4.74) log10 copies/mL vs . 4.23 (IQR 3.81–4.59) log10 copies/mL, respectively], ( P = 0.004). A total of 343 patients discontinued at least one drug of those included in the first cART regimen, more often EFV (26%) than RPV (13%), by 2 years ( P < 0.0001). After adjustment, patients treated with EFV were more likely to discontinue at least one drug for any cause [relative hazard (RH) 4.09; 95% confidence interval (CI) 2.89–5.80], for toxicity (RH 2.23; 95% CI 1.05–4.73) for intolerance (RH 5.17; 95% CI 2.66–10.07) and for proactive switch (RH 10.96; 95% CI 3.17–37.87) than those starting RPV. Conclusions: In our nonrandomized comparison, RPV was better tolerated, less toxic and showed longer durability than EFV, without a significant difference in rates of discontinuation because of failures.